Lhermitte duclos disease: what to expect during surgery? - Sanjeev Kumar (SpringerOpen, 2021)
Abstract Lhermitte and Duclos first described the dysplastic gangliocytoma of the cerebellum in 1920. In the last 100 years, its clinical presentation, radiological features, pathological characteristics, and association with Cowden syndrome have been well described. However, documentation of surgical experiences is lagging. We here describe intraoperative experience during the removal of the tumor, which could help the operating surgeon plan and mental makeup.